TITLE (PROBLEMATIKA PENYELESAIAN STUDI AKHIR MAHASISWA) - Junita, Ellmy Lia; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe dance "TITLE" was inspired by the processes of a student in writing his/her thesis with various problems that occured. This type of dance was dramatic consisting of opening, content and closing stages which was arranged in such a way to produce a dance with a story line. Beginning with past events in the process of thesis preparation, with various problems both from outside even from within her/himself covered with anger, dizziness, chaos, frustration, sadness and pressure, so that at he end all the problems were successfully overcome. Then the thesis was done with a proud heart with his/her body covered by a toga stating that the student graduated and successfully attained a bachelor's degree. In this work of "TITLE", it also applied the methods in the creation phase into a dance work including exploration, processing, application, evaluation and revision. The presentation of this work showed an interesting aesthetic performance in terms of the dance performance and also the musical accompaniment, so that this work is not only a spectacle, but also an interesting art performance. This work also combined diverse and unique choreography. The choreography that used is inseparable from daily activities mixed with pure and meaningful movements. The work was considered in its presentation so that this final work "TITLE" is formed.Â Keyword : TITLE, method and creational process, dance analyzing.